Case report: Transition from anti-CD20 therapy to inebilizumab for 14 cases of neuromyelitis optica spectrum disorder - Osborne, Benjamin; Romanow, Gabriela; Hemphill, J. Michael; Zarif, Myassar; DeAngelis, Tracy; Kaplan, Tyler; Oh, Unsong; Pinkhasov, Johnathan; Patterson, Kristina; Levy, Michael (Frontiers in Neurology, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disorder of the central nervous system characterized by recurrent, disabling attacks that affect the optic nerve, spinal cord, and brain/brainstem. While rituximab, targeting CD20-positive B-cells, is used as an off-label therapy for NMOSD, some patients continue to exhibit breakthrough attacks and/or adverse reactions. Inebilizumab, a humanized and glycoengineered monoclonal antibody targeting CD19positive B-cells, has been FDA approved for the treatment of NMOSD in adult patients who are antiaquaporin-4 (AQP4) antibody positive. Given the limited real-world data on the efficacy and safety of inebilizumab, especially in those transitioning from rituximab, a retrospective chart review was conducted on 14 NMOSD patients from seven centers. Of these, 71.4% (n=10) experienced a combined 17 attacks during rituximab treatment, attributed to either breakthrough disease (n=10) or treatment delay (n=7). The mean duration of rituximab treatment was 38.4 months (3.2 years). Notably, no subsequent attacks were observed during inebilizumab treatment (mean duration of inebilizumab treatment was 19.3 months (1.6 years), underscoring its potential as an effective treatment for NMOSD. Our data suggest that inebilizumab provides clinical benefit with effective disease control and a favorable safety profile for patients transitioning from rituximab.